Contemporary psychiatry: Volume 1 Foundations of Psychiatry, Volume 2 Psychiatry in Special Situations, Volume 3 Specific Psychiatric Disorders - Henn, Fritz A. (Springer Berlin Heidelberg Imprint: Springer, 2001)
Contemporary Psychiatry is an international textbook developed on the basis of the experience with its first three German editions - making it a work with long and distinguished tradition. It combines the German tradition of phenomenology and diagnosis going back to Kraepelin with the Anglo-American tradition and the DSM IV diagnostic system. In doing so, Contemporary Psychiatry becomes a unique source among psychiatric texts, offering a truly international approach to state-of-the-art knowledge and future perspectives of psychiatry. The four internationally renowned editors were able to aquire the leading specialists as contributors. No less than 120 authors from 10 different countries ensure an extremely high standard and guarantee the consideration of cross-cultural aspects. A special feature of Contemporary Psychiatry is that it includes chapters on psychiatric disorders caused by extreme circumstances, such as for example migration, torture, rape, violence and natural and man-made disasters
Gesehen am 12.11.2020